Spremembe ZUP terjale tudi nadgradnjo uspešnega komentarja - Koritnik, Boštjan (Javna uprava, 2022)
In 2020, the publishing house Uradni list Republike Slovenije together with the Faculty of Law of the University of Ljubljana published a commentary on the General Administrative Procedure Act (Zakon o splošnem upravnem postopku – ZUP), edited by Professor Polonca Kovač, PhD, and Erik Kerševan, PhD. The commentary, which was published in two volumes, was a great success among users, as top Slovenian experts participated in it, and with the adoption of the Act on Debureaucratisation (Zakon o debirokratizaciji – ZDeb), which also interfered with the field covered by ZUP a reason arose to upgrade the Commentary. In September 2022, both the publisher and the authors added a third volume to the set, in which the authors discuss the changes enacted by the legislature from the first edition to the end of June 2022, taking into account important case law adopted during that time. The third book of the commentary was presented to the public at a round table in mid-September.
Keywords: Kovač, Polonca, Kerševan, Erik (ur.): Komentar Zakona o splošnem upravnem postopku (ZUP); ocene in poročila; upravni postopek; ZUP